GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 56 species occurrences available in GBIF matching the query: TaxonKey: Pinus silvestris HasCoordinate: true. The dataset includes 56 records from 11 constituent datasets: 1 records from NSW herbarium collection. 13 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 4 records from Water Colours of Fungi by Konrad Schieferdecker at the Botanische Staatssammlung München. 9 records from MfN - Fossil plants (Cenophytic). 1 records from FURB - Herbário Dr. Roberto Miguel Klein. 1 records from JOIw - Xiloteca Joinvillea. 2 records from Paleobiology Database. 3 records from CESJ - Herbário Leopoldo Krieger. 11 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 6 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 4 records from Herbarium of Jyväskylä University Museum.
Keywords: GBIF; biodiversity; species occurrences